2020
DOI: 10.1111/jdv.16367
|View full text |Cite
|
Sign up to set email alerts
|

‘Inverse association between the total naevus count and melanoma thickness’

Abstract: Background Individuals with a high total naevus count (TNC) are at a higher risk to develop melanoma, and screening efforts have been largely focused on this group. However, some studies suggest that melanomas of patients with many nevi are thinner than those of patients with few nevi. Additionally, nodular melanoma has been associated with individuals with a low naevus count. Objective To investigate the association between TNC and melanoma Breslow thickness. Methods A two-centre retrospective study from 1 Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a study conducted by Marghoob et al, an inverse correlation between the total nevus count and cutaneous melanoma thickness was discovered [14]. Their findings demonstrated that individuals with a higher number of nevi tended to have thinner cutaneous melanomas and a higher prevalence of in situ melanomas, regardless of sex and age [11].…”
Section: Discussionmentioning
confidence: 96%
“…In a study conducted by Marghoob et al, an inverse correlation between the total nevus count and cutaneous melanoma thickness was discovered [14]. Their findings demonstrated that individuals with a higher number of nevi tended to have thinner cutaneous melanomas and a higher prevalence of in situ melanomas, regardless of sex and age [11].…”
Section: Discussionmentioning
confidence: 96%
“…According to the eight edition of the American Joint Committee on Cancer (AJCC), our MPM series has fifty in-situ CM (T0: 83%) and ten invasive CM (pT1a: 17%). Marghoob et al revealed an inverse association between the total nevus count and CM thickness, demonstrating that patients with a higher number of nevi had thinner CM and more in-situ CM, independently of sex and age [51].…”
Section: Discussionmentioning
confidence: 99%